New Models for Sustainable Logistics Internalization of External Costs in Inventory Management - Digiesi, Salvatore; Mascolo, Giuseppe; Mossa, Giorgio; Mummolo, Giovanni (SpringerBriefs in Operations Management, 2016)
XIII, 98 p. 30 illus., 4 illus. in color.